The "emergency contraception". - Di Pietro, Maria Luisa; Minacori, Roberta (Medicina e Morale, 2001)
The article dwells upon the practices defined "emergency contraception" or "postcoital contraception", that are performed after a presumed fertilising sexual intercourse, aimed to prevent the prosecution of a pregnancy, if this is already begun. The recent marketing in Italy of the pill "Norlevo" has relighted a debate, already open for a long time in international level, where strategies are in action from different corporate bodies for the diffusion of such means, until now with little results, especially among teen-agers or the women victims of rape. After having described the various products and protocols in use and to the light of the data found in the international literature, the Authors have put in evidence as, despite an anti-ovulation effect is possible, in wide part (70- 100% of the cases) the mechanism of action of these products is abortive and not contraceptive. They prevent, in fact, the continuation of the pregnancy, through the action on the corpus luteum, on the fallopian tube and, particularly, on the endometrium: these three effects interfere with the post-fertilisation phase, therefore with the development of the embryo, who is already present if the sexual intercourse has been fertile. Finally, the Authors underline the semantic manipulation done both in scientific circles and in institutional ones to improve the acceptability from the public opinion. So, it is necessary to give women a clear and objective information on the real mechanism of action of these products in comparison to a possible pregnancy.